Coronary heart disease in diabetes mellitus : risk factors and epidemiology - Carneiro, António Vaz (2018)
Cardiovascular complications in diabetic patients, especially type 2, can be classified as microvascular (renal, ophthalmologic and neurologic) and macrovascular (coronary, cerebrovascular and peripheral vascular). Type 1 and 2 diabetic patients have increased cardiovascular risk, especially for coronary artery disease. This has been well established through high-quality studies, as have interventions to ameliorate the major risk factors. The main risk factors for increased incidence of coronary artery disease in diabetic patients include hyperlipidemia, hypertension, smoking, microalbuminuria and hyperglycemia. The therapeutic approach to the type 2 diabetic patient should include--if there is no individual contraindication--diet control, physical exercise, smoking cessation and, particularly, pharmacologic interventions with antiplatelets (mainly aspirin and clopidogrel) and/or anticoagulants (warfarin), angiotensin-converting enzyme inhibitors, angiotensin II receptor antagonists, beta-blockers and anti-dyslipidemics (mainly statins), as well as oral antidiabetics (or insulin). In this paper we present and discuss the results of lowering cardiovascular risk in these patients, which should lead to a marked decrease in the incidence of coronary artery, cerebrovascular and peripheral vascular disease, with consequent improvement in prognosis.